THEORIES OF MOTIVATION AND BASIC MOTIVATIONAL CONCEPTS - Khosiyat Nazarovna Kadirova (Web of Journals Publishing, 2023)
The connection between the methodology of teaching a foreign language and linguistics has taken place throughout the history of the development of methodology as a science. This connection is obvious, since it is linguistics that develops the general methodological foundations of language learning, analyzes specific language material, and gives it a scientifically based objective interpretation.
Keywords: A person is in need when he feels physiologically or psychologically a lack of something. In accordance with the cultural order, the need may acquire the character of a specific need.